Thoracoscopic repair of recurrent CDH is associated with a significantly lower complication rate and shorter ICU and hospital stay: A Prospective, Propensity Score-Matched Analysis - Beck, Lydia; Weiß, Christel; Mohr, Christoph; Martel, Richard; Klinke Petrowsky, Michaela; Rhee, Jin; Zahn, Katrin; Schaible, Thomas; Boettcher, Michael; Elrod, Julia (European journal of pediatric surgery, 2025)
Congenital diaphragmatic hernia (CDH) is a malformation that significantly impacts neonatal morbidity and mortality. Recurrence after surgical repair remains a potentially life-threatening long-term complication. Conventionally, recurrent CDH has been managed through open surgery. However, thoracoscopic repair (TR) represents a novel alternative for recurrent CDH as it has reduced the length of hospital stay and mortality rate in the primary CDH repair. A prospective, propensity score-matched analysis was conducted on pediatric patients who underwent recurrent CDH repair at the University Hospital Mannheim between 2013 and 2023, to compare the outcomes of laparotomy versus TR. Patients were categorized based on the surgical technique employed. Comparative analysis, including propensity scoring, encompassed outcome measures such as duration of ICU and hospital stays, rate of complications, and operative duration. In total, 703 patients were treated for CDH, of whom 69 children underwent laparotomy (56) or TR (16) for CDH recurrence. After propensity score matching, TR group demonstrated a significantly shorter duration of surgery (178 [93-311] versus 225 [113-450] min, p = 0.042), reduced ICU stay (0 [0-10] versus 1 (0-69) days, p = 0.011), and decreased overall hospital stay (6 [3-34] versus 12 [7-40] days, p = 0.001). Moreover, the postoperative complications were significantly lower in the TR group (21.43% versus 73.68%, p = 0.003). TR for recurrent CDH repair is associated with shorter operation times, reduced ICU and overall hospital stays, and fewer complications compared with laparotomy. These findings suggest that TR may be preferable for the management of recurrent CDH, warranting larger randomized controlled studies to confirm the long-term safety and efficacy of this approach.
Gesehen am 12.06.2025